FORMATION OF THE LANGUAGE AND COMMUNICATIVE COMPETENCE OF STUDENTS NON-PHILOLOGICAL SPECIALTIES - Dotsenko Оlena L. (Educological discourse, 2015)
The article considers the peculiarities of linguistic and communicative competence of students of Non-philological Profile; disclosed specifics of accounting degree communicative filling specialty in determining the scope and content of the linguistic component of the curriculum for the bachelor’s and master; proposed indicative list of disciplines linguistic cycle for students with communicative filled and unfilled communicative function.